VISUAL IMAGES OF SPACE. REVIEW OF THE GEOGRAPHY OF ART VII INTERNATIONAL CONFERENCE / ВИЗУАЛЬНЫЕ ОБРАЗЫ ПРОСТРАНСТВА. ОБЗОР VII МЕЖДУНАРОДНОЙ КОНФЕРЕНЦИИ «ГЕОГРАФИЯ ИСКУССТВА» - Lavrenova Olga A. / Лавренова О.А. (Наука телевидения)
The Geography of Art International Scientific Conference has a long history. Geography of Art began in 1994 and was originally conceived as a purely publishing project. In 2009, the first conference was held under the auspices of the Likhachev Russian Research Institute for Cultural and Natural Heritage and its director Yuri A. Vedenin. The topics at the conferences are traditionally very diverse, but the “protagonist” of all discussions, debates, and subsequent collections is invariably space, in all its guises, and its interaction with culture. The original subjects such as the geography of art schools and traditions and the placement of artifacts on the earth’s surface have over time been supplemented by conceptual questions of the construction of spatial images in painting, literature, and cinema. Over the past few years, the conference has been organized by the Institute of Scientific Information on Social Sciences of RAS, the Russian Academy of Arts, GITR Film and Television School, and the Russian State University for the Humanities. In 2021, for the first time, the conference was arranged in a hybrid format: some sessions were held in person at the Russian Academy of Arts and GITR, while some discussions were convened online. This made it possible to significantly expand the geography of our participants. An important topic was brought up—the possibility of generating images of space and transforming the spatial picture of the world by different types of art, including screen art, creating new meanings of places and regions. A separate section was devoted to the concepts of space and the corresponding images in digital media, cinematography and photography. The section discussed the peculiarities of national cinematography from the point of view of forming the country’s image, which can play a significant role in intercultural communication, and regional images created with the help of photography and IT-technology as an attractor in the formation of recreational flows. Among other things, the conference covered the specifics of space perception in the era of digitalization, the creation of representations, and spectacularity. A separate topic was the construction of narrative topoi within the framework of different versions of screen adaptations of the same work. All discussions complemented each other in creating a three-dimensional picture of spatial images by means of digital and screen arts, generating a modified reality supplemented by photo and film visualizations. Международная научная конференция «География искусства» имеет долгую историю. Проект «География искусства» начался в 1994 году и сначала был исключительно издательским. В 2009 году была проведена первая конференция под эгидой Института культурного и природного наследия им. Д.С. Лихачева и его директора Ю.А. Веденина. Проблематика конференции традиционно очень разнообразная, но «главный герой» обсуждений, дискуссий и последующих сборников — неизменно пространство, во всех его ипостасях, и его взаимодействие с культурой. Первоначальные темы географии художественных школ и традиций и размещение артефактов на земной поверхности со временем дополнилась концептуальными вопросами конструирования пространственных образов в живописи, литературе, кино. Организаторами конференции в последние несколько лет являются Институт научной информации по общественным наукам РАН, Российская академия художеств, Институт кино и телевидения (ГИТР), Российский государственный гуманитарный университет. В 2021 году конференция впервые прошла в гибридном формате — часть заседаний состоялись очно в РАХ и ГИТРе, часть обсуждений была проведена онлайн. Это дало возможность существенно расширить географию участников. Важная тема — возможности сотворения образов пространства и преображения пространственной картины мира разными видами искусства, в том числе и экранными, создание новых смыслов мест и регионов. Отдельная секция была посвящена обсуждению концептов пространства и соответствующих образов в цифровых медиа, кино- и фотоискусстве. На секции обсуждались особенности национального кинематографа с точки зрения формирования имиджа страны, способного сыграть значительную роль в межкультурной коммуникации, региональные образы, созданные с помощью фотографии и IT-технологий, как аттрактор в формировании рекреационных потоков. Рассматривались особенности восприятия про-странства в эпоху цифровизации, создание репрезентаций, проблема зрелищности. Отдельной темой была проблема конструирования топосов повествования в рамках разных вариантов экранизации одного и того же произведения. Все обсуждения дополняли друг друга в создании объемной картины пространственных образов силами цифровых и экранных искусств, в создании видоизмененной реальности, дополненной фото- и киновизуализациями.